(untitled) (Contemporary Journal of Social Science Review, 2025)
The modern Muslim Ummah is facing a complex crisis, which is intellectual sluggishness, spiritual disorientation, and socio-political stagnation. According to Allama Muhammad Iqbal the erosion of Khudi- the dynamic principle of selfhood is the major cause of this decline. This study explores the crisis of Khudi in the Muslim Ummah and reevaluates the philosophical thoughts of Iqbal as a resource of restoring the dynamism of Muslims. The study also identifies the way in which the death of desire (ishq), action (amal), creative thought and educational purpose have undermined Muslim selfhood using qualitative textual analysis of Iqbal poetry and prose. Using Islamic philosophical doctrines like khilafat, ijtihad, and moral agency, the research claims that the synthesis of spirituality and material activities by Iqbal is a good roadmap that can be used by Muslims in the contemporary world.